Optimization of Surface Sterilization Protocol by Using Bleach for Musang King Durian - Tang, Ye-Fang (Universiti Malaysia Sarawak (UNIMAS), 2018)
Durian (Durio zibethinus), is a flowering plant in the Bombacaceae family. Currently, the conventional breeding method is unable to fulfill the increasing demand of Musang King durians due to being relatively time-consuming. Thus, propagation through the tissue culture technique can increase the production and meet increased market demand. The application of tissue culture requires sterile and living explants. The objective of this study was to investigate the optimal surface sterilization techniques for the leaves ofMusang King. The leaves from the grafted Musang King seedlings were sterilized by using different concentrations of Clorox (0 % (control), 30 %, 40 %, 50 % and 60 %) with different exposure times (40 and 50 minutes). The percentage of sterile explants and the percentage of browning explants were recorded at 7, 14 and 21 days after culture. All treatments were carried out in three replicates using five samples for each replication. The result showed that using 60 % Clorox for 50 minutes, which gave the highest percentage of sterile explants, 40.00±52.92 %, while the treatment with 40 % of Clorox for 40 minutes gave the lowest percentage of sterile explants, which was 6.67±11.55 %. The 60 % of Clorox for 40 minutes had 6.67±11.55 % of browning explants.